Thermomechanical, crystallization and melting behavior of plasticized poly (Lactic acid) nanocomposites - Izan Roshawaty Mustapa (Tanjung Malim, 2021)
Thermomechanical, crystallization and melting behavior of plasticized poly (Lactic acid) nanocomposites by Izan Roshawaty Mustapa